A mobile app intervention to support nutrition education for heart failure management: co-design, development and user-testing - Bridve Sivakumar; Maria Ricupero; Anisha Mahajan; Katherine Jefferson; John Wenger; Jillianne Code; Alex Theodorou; JoAnne Arcand (BMC Nutrition)
Abstract Background Mobile apps show promise in supporting patients with heart failure (HF) in adhering to dietary guidelines for sodium and fluid. Though numerous apps to support HF management exist, only a few have dedicated features to support dietary adherence. Objectives To describe the process and outcomes from the development and testing of Sodium Navigator HF , a mobile app intervention to engage patients with HF in dietary education and adherence. Methods Background research in app development, behaviour change, nutrition and qualitative interviews with patients and healthcare providers informed app content and design. Weekly team meetings were held to establish learning objectives, content, and features of the app until a prototype was developed and approved by the research team. Using a quasi-experimental mixed-methods design, patients with HF (≥ 18 years) evaluated the prototype via one-on-one online user-testing sessions. App engagement, satisfaction, and usability were measured using a 12-question patient-reported Likert-scale questionnaire. Participant feedback on app content and features was gathered using qualitative interviews. Results Six educational modules (dietary sodium recommendations, contributors of sodium in the diet, nutrition labelling, lowering dietary sodium, fluid restriction and goal setting), ten behaviour change techniques (e.g., feedback on behaviour, social support) and gamified components (i.e., avatar, point-system) were integrated into the app. Participants with HF (n = 10, 56±15 years, 80% women) enjoyed using the app (90%), strongly agreed that the information was meaningful and useful for their general health (80%) and was easy to use (70%). Conclusion Results demonstrate the potential of Sodium Navigator HF to support patients with dietary education and adherence for HF management.